FACTORS INFLUENCING FRUIT CONSUMPTION AMONG UNDERGRADUATES IN OBAFEMI AWOLOWO UNIVERSITY, ILE-IFE, OSUN STATE, NIGERIA - Fadeiye, E. O.; Popoola, B. R.; Emuoke, D. K.; Adeoye, T. A.; Ogundana, M. T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
This study assessed types of fruit consumed, frequency of consumption and factors influencing consumption of fruit among undergraduates in Obafemi Awolowo University, Ile-Ife, Nigeria. Multistage random sampling technique was used to select 20 respondents each from 13 Faculties of the University making a total of 260 respondents. A well-structured questionnaire was used to collect information on socio-economic characteristics, types of fruit available and consumed, frequency of consumption and factors influencing fruit consumption. Descriptive statistics were used to analyze data, while correlation analysis was used to test the hypothesis. The results showed that 43.8% of the respondents were male and 56.2% were female. The mean age was 21.05±2.7 years. The fruits that were readily available with high percentage of weekly consumption were orange (95.8%), banana (91.9%), apple (77.3%), watermelon (75.8%), pineapple (70.0%), tangerine (66.2%), and pawpaw (50.4%). Likeness (r= 0.289, p= 0.0001), taste (r= 0.206, p= 0.001), appearance (r= 0.145, p= 0.020), health condition (r= 0.141, p= 0.023), season (r= 0.292, p= 0.0001), information by family and friends (r= 0.247, p= 0.0001), texture (r= 0.190, p= 0.002), price (r= 0.212, p= 0.001) and nutritional benefits (r= 0.201, p= 0.001) were factors that had positive relationship with frequency of fruit consumption as revealed by correlation analysis. Factors such as likeness, taste, appearance, health condition, season, available information, texture, price and nutritional benefits influenced consumption of fruit consumed. Nutrition intervention programs and policy should continue to aim at improving consumption of fruits in tertiary institutions to promote healthy eating behaviour.